Factors influencing the intention to choose Islamic home financing among muslim community in Kuantan, Pahang / Hafiz Sulaiman - Sulaiman, Hafiz (Faculty of Business Management, University Teknologi MARA, 2018)
This paper aim to find out the main factors influencing the intention to choose Islamic home financing among Muslim community in Kuantan, Pahang. Several factors had been chosen in this research such as religious belief, social influence, perceived behavioral control, and service quality. The sample of this study comprised of 100 respondents among Muslim community in Kuantan through survey using questionnaire. The data was distributed in April and May 2018. The stratified random sampling technique was utilised. The descriptive analysis, reliability test, correlation test, and regression analysis were to be conducted to collect the necessary data. The data was processed and analysed by using the Statistical Package for Social Sciences (SPSS). The results of this study shows that religious belief and perceived behavioral control are the two factors influencing the intention to choose Islamic home financing among Muslim community in Kuantan, Pahang.